Maternal depression symptomatology and child well-being outcomes : limited evidence for a causal relationship - Escobal, Javier (2016)
The paper explores whether or not there is evidence for a causal link between maternal depression symptomatology and child well-being. Considering three rounds of data from the Peruvian Young Lives (PYL) longitudinal study sample, the paper explores this relationship by using the SRQ-20 instrument, which is typically used as a screening tool for common mental disorders, and by collecting information about mothers’ socioeconomic characteristics and their children’s well-being outcomes. We found a low correlation of SRQ-20 scores across rounds, suggesting that the instrument may be capturing short-term depression or anxiety symptoms rather than chronic mental illness. Furthermore, the SRQ-20 instrument is correlated both with characteristics of the mother and with child well-being indicators, which change over time (nutritional, health, and educational outcomes as well as feelings and attitudes). The study shows that the magnitude of the relationship between the mental health indicator and the child well-being outcomes may be severely biased in a regression that neglects the possible endogeneity of the mental health indicator. Finally, besides maternal age, education, and ethnicity background, socioeconomic shocks are a key determinant of both depression and anxiety symptoms as well as of child well-being outcomes in the first year following birth of the child (PYL round one), where SRQ-20 scores were the highest.